ROLE OF THE REPUBLIC OF TURKEY AND THE UNITED KINGDOM OF GREAT BRITAIN AND NORTHERN IRELAND IN CURRENT CRISIS IN AP KOSOVO AND METOHIJA (Heritage, 2026)
Observed through a historical prism, the crisis in the Kosovo and Metohija region of Serbia is determined by geopolitical interests of regional and global powers, historic processes and ethnographic changes, in which constantly, but with varying intensity, Albanian and Serbian people confront and defend each other’s right over the territory. The NATO aggression in 1999 on the Federal Republic of Yugoslavia (FRY) and the ensuing proclamation of “Kosovo“ independence in 2008, incited and encouraged the Albanian political elites to act in accordance with the Prizren League Declaration from 1878 so as to undertake intensified measures for the establishment of Great Albania, which in line with the Albanian strategic culture would foster the principles of fascist ideology “One state, one language, one nation, one religion“. To prove that such an ideology is conducted in the territory of Kosovo and Metohija, we mention several facts reflected in the violence committed daily towards Serbian and other, non-Albanian population, along with their properties, cultural and religious bulidings, which has led to a shift in national structure and systematic destruction of Serbian cultural heritage. The subject matter of this paper covers the wider context of the expressed interests of Turkey and the United Kingdom of Great Britain and Northern Ireland (hereinafter: Great Britain) in contemporary security circumstances, characterised by the presence of hybrid threats with focus on the Autonomous Province of Kosovo and Metohija (hereinafter: AP KiM) within the security agenda of these powers.
Keywords: Great Britain, AP KiM, Republic of Serbia, hybrid war, instruments of national power, national interests.